Linking personality and emotional labor: The mediating role of relationship conflict and conflict management styles - Alia Qadir; Muhammad Majid Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
In business organizations, a number of employees with different personalities work together. During their daily interactions with one another, conflicts emerge due to their diverse personalities and personal differences. However, they are somehow required to work together and along with that, are demanded, by the management, to interact nicely with customers and colleagues, which at times may leads them to pretend positive emotions and feelings; hence suffer emotional labor. Emotional labor is a new concept in business research. It is said to be a product of the rapid growth of service industry. It is proven to have detrimental impact upon the employee psychological and physical health and resultantly on their performance. So, emotional labor has become a new challenge for the modern managers and therefore, they are trying to find ways to reduce or eliminate it. The purpose of this study is to empirically test the mediating role of relationship conflict and conflict management styles on the relationship of personality and emotional Labor. In this cross-sectional study, respective data is collected from randomly selected 450 bank managers through self-administered questionnaires. Structural equation modeling technique with AMOS software is used for data analysis. The results show that relationship conflict and conflict management styles fully mediate the relationship between personality and emotional Labor. This study will open new vistas of research by proving that emotional labor can be controlled and reduced by using appropriate conflict management style and by verifying the pivotal role of personality in relation to emotional labor, relationship conflict and the choice of conflict management style.
Keywords: 330; personality; emotional Labor; relationship conflict and conflict management styles